IMPLEMENTATION OF THE PRINCIPLE OF BEST INTERESTS FOR CHILDREN IN THE JUVENILE CRIMINAL JUSTICE SYSTEM: A CRITICAL ANALYSIS OF THE KISARAN DISTRICT COURT DECISION NUMBER 21/PID.SUS-ANAK/2025/PN KIS - Amalia Anjani; Atikah Rahmi (PT. Sinergi Legal Publisher, 2026)
The principle of the best interests of the child is a fundamental principle in the juvenile criminal justice system, as regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This study aims to analyze the application of these principles to the Kisaran District Court Decision Number 21/Pid.Sus-Anak/2025/PN KIS, which has sparked controversy in Batu Bara Regency. This case has garnered public attention because it involved a child as the perpetrator of a crime that resulted in the victim's death. The prosecutor's demand and the judge's decision both imposed a 7-year prison sentence. The victim's family considered the decision too lenient and did not reflect a sense of justice, while positive law in Indonesia stipulates that the potential criminal penalty for children is half the maximum penalty applicable to adults. This study employed normative legal research methods with statutory, case-based, and conceptual approaches. The results indicate that the judge's decision aligns with the national legal framework oriented toward child protection, but still leaves a tension between restorative justice for child perpetrators and the retributive justice expected by the victim's family. These findings emphasize the need for a balance between protecting children's rights and being sensitive to the community's sense of justice in handling juvenile criminal cases. Keywords: Best Interests of the Child, Juvenile Criminal Justice System, Kisaran District Court Decision